Disruption of CRAF-mediated MEK activation is required for effective MEK inhibition in KRAS mutant tumors - Lito, Piro (2014)
MEK inhibitors are clinically active in BRAF(V600E) melanomas, but only marginally so in KRAS-mutant tumors. Here we found that MEK inhibitors suppress ERK signaling more potently in BRAF(V600E)- than in KRAS-mutant tumors. To understand this, we performed an RNAi screen in a KRAS-mutant model and found that CRAF knockdown enhanced MEK inhibition. MEK activated by CRAF was less susceptible to MEK inhibitors than when activated by BRAF(V600E). MEK inhibitors induced RAF-MEK complexes in KRAS mutant models, and disrupting such complexes enhanced inhibition of CRAF-dependent ERK signaling. Newer MEK inhibitors not only target MEK catalytic activity, but also impair its reactivation by CRAF: either by disrupting RAF-MEK complexes or by interacting with Ser 222 to prevent RAF-mediated phosphorylation in the complex.